Zircon U-Pb ages and Hf isotope data from the Kukuluma Terrain of the Geita Greenstone Belt, Tanzania Craton: Implications for stratigraphy, crustal growth and timing of gold mineralization. (March 2018) - Kwelwa, S.D.; Sanislav, I.V.; Dirks, P.H.G.M.; Blenkinsop, T.; Kolling, S.L.
Abstract: The Geita Greenstone Belt is a late Archean greenstone belt located in the Tanzania Craton, trending approximately E-W and can be subdivided into three NW-SE trending terrains: the Kukuluma Terrain to the east, the Central Terrain in the middle and the Nyamullilima Terrain in the west. The Kukuluma Terrain, forms a NW-SE trending zone of complexly deformed sediments, intruded by the Kukuluma Intrusive Complex which, contains an early-syntectonic diorite-monzonite suite and a late-syntectonic granodiorite suite. Three gold deposits (Matandani, Kukuluma and Area 3W) are found along the contact between the Kukuluma Intrusive Complex and the sediments. A crystal tuff layer from the Kukuluma deposits returned an age of 2717 ± 12 Ma which can be used to constrain maximum sedimentation age in the area. Two granodiorite dykes from the same deposit and a small granodiorite intrusion found along a road cut yielded zircon ages of 2667 ± 17 Ma, 2661 ± 16 Ma and 2663 ± 11 Ma respectively. One mineralized granodiorite dyke from the Matandani deposit has an age of 2651 ± 14 Ma which can be used to constrain the maximum age of the gold mineralization in the area. The 2717 Ma crystal tuff has zircon grains with suprachondritic 176 Hf/ 177 Hf ratios (0.28108–0.28111 at 2717 Ma) and positive (+1.6 to +2.6) εHf values indicating derivation from juvenile mafic crust. Two of the granodiorite samples have suprachondritic 176 Hf/ 177 Hf ratios (avg. 0.28106 and 0.28107 at 2663 and 2651 Ma respectively) and nearly chondritic εHf values (avg. −0.5 and −0.3 respectively). The other two granodiorite samples have chondritic 176 Hf/ 177 Hf ratios (avg. 0.28104 and 0.28103 at 2667 and 2661 Ma respectively) and slightly negative εHf values (avg. −1.1 and −1.5 respectively). The new zircon age and isotope data suggest that the igneous activity in the Kukuluma Terrain involves a significant juvenile component and occurred within the 2720 to 2620 Ma period which, is the main period of crustal growth in the northern half of the Tanzania Craton. Graphical abstract: Highlights: Kukuluma Terrain forms the eastern part of the Geita Greenstone Belt and hosts three major gold deposits. The main period of deformation and intrusive activity occurred between 2700 Ma and 2650 Ma. Crustal growth occurred between 2720 Ma and 2620 Ma from mainly a juvenile source. The maximum age of gold mineralization is 2650 Ma.